2020
DOI: 10.1038/s41594-020-0504-7
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying the dynamics of IRES and cap translation with single-molecule resolution in live cells

Abstract: Viruses use IRES sequences within their RNA to hijack translation machinery and thereby rapidly replicate in host cells. While this process has been extensively studied in bulk assays, the dynamics of hijacking at the single-molecule level remain unexplored in living cells.To achieve this, we developed a bicistronic biosensor encoding complementary repeat epitopes in two ORFs, one translated in a Cap-dependent manner and the other translated in an IRESmediated manner. Using a pair of complementary probes that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…4B, C ). This range is consistent with the range we recently measured using a different reporter without BoxB stem loops 23 . These data therefore demonstrate Ago2 tethering does not impede translation elongation compared to the β-gal control.…”
Section: Resultssupporting
confidence: 92%
“…4B, C ). This range is consistent with the range we recently measured using a different reporter without BoxB stem loops 23 . These data therefore demonstrate Ago2 tethering does not impede translation elongation compared to the β-gal control.…”
Section: Resultssupporting
confidence: 92%
“…The interaction between eIF4G and PABPC is well characterized and provides a physical link connecting both ends of the mRNA, and some studies are able to catch a glimpse of possible circular structures of mRNAs in fixed tissues ( Christensen et al, 1987 ) or in vitro ( Wells et al, 1998 ). However, recent single-molecule imaging studies in mammalian cells question the widespread existence of mRNA closed-loop structures ( Adivarahan et al, 2018 ; Koch et al, 2020 ). Our finding that depletion of PABPC had minimal impact on TE in mammalian cell lines supports a model in which pervasive eIF4G–PABPC-associated looping of mRNAs is generally lacking in uncoupled systems.…”
Section: Discussionmentioning
confidence: 99%
“…[ 91 ] Similarly, recent single‐molecule experiments revealed that translation of a dORF that was initiated by an IRES tended to enhance cap‐dependent initiation at a further upstream ORF, presumably due to changing the structure of the mRNP under translation. [ 92 ]…”
Section: Reinitiation and Regulation Of Gene Expression By Uorfs And ...mentioning
confidence: 99%
“…[91] Similarly, recent single-molecule experiments revealed that translation of a dORF that was initiated by an IRES tended to enhance cap-dependent initiation at a further upstream ORF, presumably due to changing the structure of the mRNP under translation. [92] Since uORFs can control translation of coding sequences due to the tendency for reinitiation to occur after their translation terminates [93] ,…”
Section: Reinitiation and Regulation Of Gene Expression By Uorfs And ...mentioning
confidence: 99%